Spectral analysis of electroencephalography changes after choking in judo (juji-jime) - Rau, R.; Raschka, C.; Brunner, K.; Banzer, W. (Medicine & Science in Sports & Exercise, 1999)
PURPOSE: The present study was carried out to investigate possible electroencephalographic changes induced by choking in judo (shime-waza) by means of spectral analysis and brain mapping. METHODS: Power spectral changes in Electroencephalography (EEG) were recorded in six experienced judoka who underwent a choking trial with a "shime-waza choking" technique called juji-jime. RESULTS: A significant increase of global field power in the delta-and theta-range occurred, while physiological alpha-power decreased. These changes in the low-frequency range reached a statistically significant level within a time span up to 20 s after choking, which was performed at an average choking time of 8 s. In no case did choking provoke neuropsychological symptoms. Yet, spectral EEG-analysis revealed subclinical changes of brain function. CONCLUSIONS: Choking in judo may induce subclinical electroencephalographic perturbations. The extent and duration can be objectified by means of spectral analysis of EEG data, global field power computation, and brain-mapping representation.